2022
DOI: 10.1111/ibi.13137
|View full text |Cite
|
Sign up to set email alerts
|

Using photographic records to quantify accuracy of bird identifications in citizen science data

Abstract: Citizen science data are increasingly used for biodiversity monitoring. However, concerns are often raised over the accuracy of species identifications in citizen science databases, as data are collected mostly by non-professionals. Misidentifications can simultaneously generate two error types: false positives (erroneous reports of a species) and false negatives (lack of reports of the misidentified species). Large-scale assessments of identification errors should provide insights into the strengths and weakn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
14
0
2
Order By: Relevance
“…The use of measurements taken from photographs allowed us to provide a robust approach in species' assignment, as already common for individual‐based recognition methods (De Lutio et al., 2021; Ferreira et al., 2020), a factor that is key to the use of citizen‐science records, particularly in the case of cryptic species (Gorleri et al., 2022). We acknowledge that our approach is only applicable to cryptic species with identifiable morphological differentiation that correspond to levels 2 and 3 of the classification proposed by Chenuil et al., 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of measurements taken from photographs allowed us to provide a robust approach in species' assignment, as already common for individual‐based recognition methods (De Lutio et al., 2021; Ferreira et al., 2020), a factor that is key to the use of citizen‐science records, particularly in the case of cryptic species (Gorleri et al., 2022). We acknowledge that our approach is only applicable to cryptic species with identifiable morphological differentiation that correspond to levels 2 and 3 of the classification proposed by Chenuil et al., 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Citizen – or community – science is increasingly emerging as a key approach for biodiversity data collection, fostering the study of wildlife worldwide, and namely addressing the urge of clarifying and understanding species' distributions for ecological studies and conservation (Campanaro et al., 2017). The reliability of citizen‐science derived data is often questioned, yet numerous studies indicate that citizen science can provide high‐quality data, comparable to those collected by trained scientists (Aceves‐Bueno et al., 2017), even though their applicability to the study of cryptic species remains limited (Gorleri et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As a rule, the data are not the result of systematic studies and are made by an array of observants of different skill levels. Callaghan, et al [ 38 ] showed that CS data are usually biased towards larger and more common species, which are mostly correctly identified [ 29 ]. Therefore, for specific scientific questions, CS data may be sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Most lists of CS data have also been found to be mostly complete at the family level when compared to professional data and provide prompt records for new emerging species [ 28 ]. Since most species are correctly identified as well [ 29 ], this means CS data can be a good predictor for species richness [ 20 ]. Robinson, et al [ 30 ] showed a count difference biased toward undercounts of contributors to the CS platform eBird compared to a professional ornithologist.…”
Section: Introductionmentioning
confidence: 99%
“…Another component of capability that has attracted research attention is the ability of people to identify different kinds of animals (and plants). In general, people's identification abilities have been found to be highly variable but on average quite poor, especially in wealthier countries (e.g., Austen et al., 2016; Bashan et al., 2021; Dallimer et al., 2012; Härtel et al., 2023; Pilgrim et al., 2008; Prokop & Rodak, 2009; Robinson et al., 2016; Shwartz et al., 2023; Vaughn et al., 2022), although very much better for those for whom such skills are more important (e.g., Gorleri et al., 2023; Scott & Hallam, 2002). There are some significant qualifiers.…”
Section: Internal Factorsmentioning
confidence: 99%